Regenerasi Website Desa Klatakan Untuk Meningkatkan Efisiensi Pelayanan Publik Dan Pengelolaan Data Melalui Pembaharuan Domain - Ida Fitriana Ambarsari; Mohammad Rizal; Dilafatul Kholilah; Yunita Yunita; Zainal Abidin (I-Com: Indonesian Community Journal, 2025)
The advancement of information and communication technology (ICT) has brought significant changes to public service systems, including at the village level. The Community Empowerment-Based Service Program (PBPMD) in Klatakan Village, Situbondo Regency, was carried out in response to the suboptimal use of the village website, which previously experienced technical obstacles such as inactive domains and limited content management. This activity aims to regenerate the village website. The method employed includes updating the official “desa.id” domain, redesigning the website interface to make it more responsive and informative, and providing intensive training for village officials and youth cadres on website operation and digital content management. The results show that the website reactivation was successfully implemented, and the new design has facilitated easier access to digital-based public services. In addition, the two-session training provided a significant impact on improving the technical skills of villagers in managing and utilizing the website as a medium for communication, information, and independent public services.